Global distribution capabilities, origin destination control and dynamic pricing - Isler, Karl (Henry Stewart Talks, 2009)
Price discrimination, Traditional distribution, Origin destination availability, Traditional distribution of fares, Internet distribution, Reaction to traditional carriers, Integrated pricing and revenue management, The new control mechanism, Real time dynamic pricing via global distribution, Global distribution improvements for dynamic pricing, Point of sale and point of commencement, Round trips and one-ways, Are booking classes a necessary evil?